2017
DOI: 10.1093/intqhc/mzx061
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events related to hospital care: a retrospective medical records review in a Swiss hospital

Abstract: The incidence of preventable AE in patients hospitalized in one Swiss hospital is comparable to previously reported rates. Further, patient safety improvement is needed, especially among older patients, and for surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 28 publications
2
38
2
6
Order By: Relevance
“…Of the remaining 307 studies, 241 were excluded after reviewing the full article. A total of 66 studies reporting 70 independent samples were included in the review 1732333435363738394041424344454647484950515253545556575859606162636465666768697071727374757677787980818283848586878889909192939495969798Figure 1. shows the study flow for the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 307 studies, 241 were excluded after reviewing the full article. A total of 66 studies reporting 70 independent samples were included in the review 1732333435363738394041424344454647484950515253545556575859606162636465666768697071727374757677787980818283848586878889909192939495969798Figure 1. shows the study flow for the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…As data sources, electronic health records are rich but often somewhat chaotic, adding to the complexity of adverse event detection. Terms used to report fall events vary between settings, which could limit an algorithm’s performance [ 29 ]. However, in our validation study, the same unmodified version of our algorithm returned excellent results in 3 clinical departments on 2 sites (using 2 electronic health record systems) [ 30 - 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study is subject to several notable limitations. First, the quality of any algorithm’s results cannot surpass that of the documentation upon which it is based, that is, the quality and the completeness of the documentation define the limits of the algorithm’s performance [ 17 , 29 ]. Therefore, heavy workloads, which influence documentation quality, also influence our algorithm’s capacity to detect falls.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the actual amount of avoidable patient harm has been controversially discussed [ 17 ], [ 18 ], [ 19 ], [ 20 ], [ 21 ], [ 22 ], [ 23 ], [ 24 ], [ 25 ], [ 26 ], [ 27 ], [ 28 ], [ 29 ], [ 30 ], [ 31 ], [ 32 ]. However, a current review about the results of all studies that have been conducted based on retrospective file analyses revealed that avoidable harm occurs in at least 5% of all hospital stays ([ 33 ], here figure 2). Furthermore, a current systematic review mentions an average of 2-3 critical events per 100 outpatient medical consultations and/or patient files of the included studies.…”
Section: Introductionmentioning
confidence: 99%